Humans not heroes: Canadian emergency physician experiences during the early COVID-19 pandemic. Issue 2 (17th October 2022) - Tran, Anna; Wallner, Clare; de Wit, Kerstin; Gérin-Lajoie, Caroline; Ritchie, Kerri; Mercuri, Mathew; Clayton, Natasha; Boulos, Mary; Archambault, Patrick; Schwartz, Lisa; Gray, Sara; Chan, Teresa Man-Yee
Abstract : Background: The pandemic has upended much clinical care, irrevocably changing our health systems and thrusting emergency physicians into a time of great uncertainty and change. This study is a follow-up to a survey that examined the early pandemic experience among Canadian emergency physicians and aimed to qualitatively describe the experiences of these physicians during the global pandemic. The study was conducted at a time when Canadian COVID-19 case numbers were low. Methods: The investigators engaged in an interview-based study that used an interpretive description analytic technique, sensitised by the principles of phenomenology. One-to-one interviews were conducted, transcribed and then analysed to establish a codebook, which was subsequently grouped into key themes. Results underwent source triangulation (with survey data from a similar period) and investigator-driven audit trail analysis. Results: A total of 16 interviews (11 female, 5 male) were conducted between May and September 2020. The isolated themes on emergency physicians' experiences during the early pandemic included: (1) disruption and loss of emergency department shift work; (2) stress of COVID-19 uncertainty and information bombardment; (3) increased team bonding; (4) greater personal life stress; (5) concern for patients' isolation, miscommunication and disconnection from care; (6) emotional distress. Conclusions: Canadian emergency physicians experienced emotional and psychological distress during the early COVID-19 pandemic, at a time when COVID-19 prevalence was low. This study's findings could guide future interventions to protect emergency physicians against pandemic-related distress.